Aquisição de implicaturas escalares: considerações teóricas e experimentais com base em casos típicos e atípicos - Torres, Jonathan Silva (Universidade Federal de São Carlos, 2018)
Almost 60 years ago, when H. P. Grice sketched a distinction between “presupposition” and “implicature” we can say that, even with its origins in analytic philosophy, modern linguistic pragmatics was born. The study of human communication had already received attention in philosophy by authors like John Austin and John Searle through the Speech Acts Theory and, although the latter had already proposed an account about the intentions of the speakers, present in the communicative acts, it is in the seminal work of Grice (1975) that intention is described in a systematic way, allied to linguistic phenomena. It is also in Grice’s work that the study of the implicatures begun, which has received attention from linguists until today under “scalar implicatures”. A number of theories have been proposed to try to account for the phenomenon and from the beginning of the twenty-first century, these theories have been increasingly put to the test by means of experimental studies in order to verify how the speakers, with either typical or atypical development, acquire or process these implicatures. This master’s thesis is committed to a presentation of these theories and related experiments in order to formulate a critical debate about its theoretical-experimental adequacy to account for the phenomenon.
Acquisition of scalar implicatures: experimental and theoretical considerations based on typical and atypical cases
Keywords: Implicaturas escalares; Aquisição da linguagem; Processamento linguístico; Desenvolvimento típico; Desenvolvimento atípico; Scalar implicatures; Language acquisition; Linguistic processing; Typical development; Atypical development; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::PSICOLINGUISTICA